Efficacy and safety of neoadjuvant PD-1 inhibitors or PD-L1 inhibitors for muscle invasive bladder cancer: a systematic review and meta-analysis - Huang, Shibo; Huang, Yanping; Li, Chunyan; Liang, Yiwen; Huang, Miaoyan; Luo, Raoshan; Liang, Weiming (Frontiers in Immunology, 2024)
Introduction This meta-analysis aims to evaluate the efficacy and safety of neoadjuvant PD-1 inhibitors or PD-L1 inhibitors [PD-(L)1 inhibitors] for muscle-invasive bladder carcinoma (MIBC). Materials and methods Four databases (Medline, Embase, Web of Science, and 21 CENTRAL) were searched for articles studying neoadjuvant PD-(L)1 inhibitors for MIBC. The search time period was from the establishment of each database to 21 July 2023. Meta-analyses of pCR, pPR, Grade≥ 3 irAEs rate, RFS, and OS were performed. Results In total, 22 studies were included for meta-analysis. The overall pooled pCR of neoadjuvant PD-(L)1 inhibitors was 0.36 (95%CI=0.30–0.42, p=0.00). In subgroup meta-analysis, the pooled PCR of PD-(L)1 inhibitors alone, PD-(L)1 inhibitors plus other ICI, and PD-(L)1 inhibitors plus chemotherapy was 0.27 (95%CI=0.19–0.35, p=0.1), 0.41 (95%CI=0.21–0.62, p=0.01), 0.43 (95%CI=0.35–0.50, p=0.06), respectively. The overall pooled pPR of neoadjuvant PD-(L)1 inhibitors was 0.53 (95%CI=0.46–0.60, p=0.00). In subgroup meta-analysis, the pooled pPR of PD-(L)1 inhibitors alone, PD-(L)1 inhibitors plus other ICI, and PD-(L)1 inhibitors plus chemotherapy was 0.36 (95%CI=0.22–0.51, p=0.01), 0.51 (95%CI=0.39–0.62, p=0.43), and 0.61 (95%CI=0.53–0.69, p=0.01), respectively. Kaplan–Meier curves for OS and RFS were reconstructed, but there was no significant difference among three groups in terms of OS or RFS. The pooled result of Grade≥ 3 irAEs rate for neoadjuvant PD-(L)1 inhibitors was 0.15 (95%CI=0.09–0.22, p=0.00%). In subgroup analysis, the pooled result of Grade≥ 3 irAEs rate for PD-(L)1 inhibitors alone, PD-(L)1 inhibitors plus other ICI, and PD-(L)1 inhibitors plus chemotherapy was 0.07 (95%CI=0.04–0.11, p=0.84), 0.31 (95%CI=0.16–0.47, p=0.06), and 0.17 (95%CI=0.06–0.31, I2 = 71.27%, p=0.01), respectively. Conclusion Neoadjuvant PD-(L)1 inhibitors were feasible and safe for muscle invasive bladder cancer. Compared with PD-(L)1 inhibitors alone, PD-(L)1 inhibitors plus other ICI and PD-(L)1 inhibitors plus chemotherapy were associated with higher pCR and pPR, but higher Grade≥3 irAEs. Kaplan–Meier curves for OS and RFS indicated that neoadjuvant PD-(L)1 inhibitors had an acceptable long-term prognostic, but it was not possible to discern statistical differences between the three neoadjuvant subgroups. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023452437, identifier PROSPERO (CRD42023452437).